Investigating the relationship between empirical evidence and teacher practice in the use of songs in early years settings and primary school education in the UK. - Hamilton, C (2021)
Songs are a ubiquitous feature of early education, with recent surveys reporting that teachers use songs every day or often in UK and international primary school settings. However, there is little rigorously-gathered empirical evidence of songs’ pedagogical benefits. The stark mismatch between carefully-controlled research and teacher intuition lead to this mixed-methods investigation into how UK early years and primary teachers use songs. An online questionnaire (n=103 participants) explored teachers' self-reported purposes for using songs and planning behaviours. This was followed up by seven semi-structured interviews to explore teacher practice and thought processes regarding songs’ educational value more deeply. In particular, how song use varies across age groups taught within early years and primary school, teachers’ attitudes towards singing as a pedagogical tool, and their belief in songs’ educational value were investigated quantitatively through the questionnaire and qualitatively through the interview phases. Participants also suggested research they would like to see regarding song use in education. The discussion brings together research literature and teacher practice (as evidenced by participants’ self-report in this study) and suggests future research directions that might guide pedagogy.